A nova concepção da iniciação científica nas IFES: um estudo de caso - Bedendo, Carolina (2011)
This paper examines some of the key elements that make up the field of scientific studies on the specificity of initiation of the course of Production Engineering, Federal University of São Carlos (UFSCar), which tend to characterize it as a space where tend is the production of knowledge potentially productive. As proposed objectives for the study, we sought to understand the reasons that lead students to seek the inclusion in the practice of undergraduate research, and understand how knowledge is produced in the research activities of graduate scholars in the field of Production Engineering. In this sense, we seek here to investigate the functionality of the CNPq as a promoter of research through their edicts, in close relationship with the state policy, and the major resolutions that regulate the Institutional Program for Scientific Initiation Scholarships (PIBIC). Then we analyze how its specific UFSCar, objective in their practice the main changes that have been taking shape in higher education as a result of the changing historical rationality imposed their culture through state action.Thus, we draw here an analysis which shows that the construction of knowledge, especially that which is funded within the public university and here in the context of undergraduate research in the field of Production Engineering, aims to produce values for the capital, to increase the intellectual capital of the productive sector and deepen its competitiveness in the face of national and international markets. To this end, the university has changed its historic identity and responds to policies formulated at the national level that allocates Science and Technology (S&T) as the axis of development of the country. In this way, students are realizing their education in pursuit of a certain social prestige that research can give them, according to testimonies collected in interviews in order to turn their expectations in achieving a place in graduate school or in a prominent place in labor market, as a reward for intensified work in the dynamics of research